Treatment in prison and prospects for reintegration. JEPRAN: a study with young people in Andalusian prisons. - Sepúlveda Rubio, Francisco Javier (My University, 2023)
This study is part of the JEPRAN Project, focusing especially on the results of the interviews we conducted in prisons in Malaga, Almeria, Cadiz and Granada in relation to the treatment received in prison and the inmates' own view of the prison as an element that helps their reintegration. It is worth noting that the experience of being incarcerated can be extremely challenging for individuals. Life in prison is highly regulated, with limited personal freedoms and a lack of privacy. Inmates often experience feelings of isolation and loneliness, and may struggle with mental health issues as a result. Additionally, the culture within prisons can be violent and hostile, with a hierarchy among inmates that may lead to victimization and abuse. These factors can have a profound impact on an individual's physical and mental well-being, making it all the more critical to address the specific needs of young individuals in the prison system. The results obtained indicate that young people who enter Andalusian prisons are in a particularly vulnerable situation due to their age and the circumstances that have led them to commit crimes. Often, these young people come from disadvantaged backgrounds and have been victims of violence and abuse. In terms of their treatment in prisons, a number of issues have been identified. For example, it has been found that young people are often abused and mistreated by other inmates and sometimes also by prison staff. In addition, shortcomings have been detected in education and training programmes, as well as in medical and psychological care services. In short, this study highlights the importance of paying attention to the specific needs of young people in Andalusian prisons in order to ensure fair and humane treatment and to promote their rehabilitation and reintegration into society.
Keywords: Delincuencia juvenil - Andalucía; Presos - Rehabilitación; Prisons; Treatment; Reintegration